2005
DOI: 10.1002/bdra.20206
|View full text |Cite
|
Sign up to set email alerts
|

Gastroschisis, low maternal age, and fetal morbidity outcomes

Abstract: Low maternal age appears to be a risk factor for low birth weight and very preterm birth among gastroschisis-affected fetuses. This information is potentially useful for planning by care providers and in counseling affected parents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0
3

Year Published

2008
2008
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 0 publications
2
21
0
3
Order By: Relevance
“…The association between teenage pregnancy, smoking and the incidence of gastroschisis identified in other studies [11,18,21,23] is supported by our findings. …”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The association between teenage pregnancy, smoking and the incidence of gastroschisis identified in other studies [11,18,21,23] is supported by our findings. …”
Section: Discussionsupporting
confidence: 81%
“…This observation suggests that cigarette smoking may have an even more significant role in the older maternal population. The effects of smoking on fetal growth are well described with evidence that the impact may be even greater for infants of multiparous mothers [5,10,11,21]. …”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The correlation between young maternal age and gastroschisis is well known [13,17], although little is understood of its biologic origins. A recent epidemiologic study reported a correlation between young maternal age and low birth weight [18]; however, the impact of young maternal age or gestational age on surgical outcomes of gastroschisis itself has not been studied. Our study is the first to indicate a protective effect of the primigravida, which was also associated with teenaged pregnancy, on disease-related morbidity in gastroschisis.…”
Section: Discussionmentioning
confidence: 96%
“…The Centers for Disease Control and prevention have estimated the national prevalence for these defects to be 3.73 and 2.09 per 10,000 live birth for gastroschisis and omphalocele, respectively (2). Association with young maternal age ( < 20 yr) and environmental factors have been proposed (3,4). Khuzestan province have many oil and petrochemical complex.…”
mentioning
confidence: 99%